Regulator Non-coding RNAs: miRNA, siRNA, piRNA, lncRNA, circRNA - Ertan Altayli (National Scientific Medical Center, 2020)
Gene expression and its regulation play a central role in maintaining life and generation in all living things. According to the central dogma of genetics, DNA plays a central role in gene expression, RNA is synthesized from DNA, and protein is synthesized from RNA. According to recent research results, human DNA produces more regulator non-coding RNA than protein coding RNAs. These RNAs act as important functional regulatory molecules in various cellular processes, including chromatin remodeling, transcription, post-transcriptional modifications and signal transfer. Therefore, the regulator ncRNAs act as key regulators of physiological programs in terms of development and disease. In this review, the main structural and functional properties of miRNA, siRNA, piRNA, lncRNA and circRNA defined as regulator ncRNAs are reviewed.